GENDER CHARACTERISTICS OF THE MANIFESTATION OF A SENSE OF STRESS RESISTANCE IN ADOLESCENTS (Innovate Conferences, 2025)
This article examines the development of stress resistance during adolescence and the gender-specific characteristics associated with this process. A comparative psychological study was conducted to determine how male and female adolescents respond to stress, the psychological defense mechanisms they employ, and their levels of emotional resilience. The data reveal distinct gender differences: female adolescents tend to show higher emotional sensitivity and anxiety levels, while male adolescents are more likely to use active coping strategies or denial. Family support and social factors were found to be significant determinants of stress resistance. The findings contribute to the development of gender-sensitive approaches to enhancing adolescents' ability to cope with stress.